2019
DOI: 10.1097/md.0000000000015507
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Fu's subcutaneous needling for hemiplegic shoulder pain among stroke survivors

Abstract: Background: Hemiplegic shoulder pain (HSP) is a frequent complication after stroke and limits patients’ physical functioning of the affected arm, thus compromising their quality of life. Fu's subcutaneous needling (FSN) has been widely applied in the treatment of pain diseases in China; however, its efficacy and safety for HSP remain to be elucidated. We therefore conducted a randomized, controlled trial to summarize the current evidence on the effects of FSN on the recovery outcomes of stroke sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…NS and LR are still the basic solutions used in fluid resuscitation, but there are serious shortcomings in their application. NS is often complicated by hyperchloric acidosis, and LR can induce cell pseudohypoxia and aggravate intracellular acidosis, and neither contains energy substrates as previously described (S. Liu et al, 2019; Young et al, 2014). Previous studies have shown that LR aggravates tissue edema and multiorgan dysfunction syndrome (MODS) through lactic acidosis, inflammation, and peroxidation (Matsuo et al, 2021; Wagner et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…NS and LR are still the basic solutions used in fluid resuscitation, but there are serious shortcomings in their application. NS is often complicated by hyperchloric acidosis, and LR can induce cell pseudohypoxia and aggravate intracellular acidosis, and neither contains energy substrates as previously described (S. Liu et al, 2019; Young et al, 2014). Previous studies have shown that LR aggravates tissue edema and multiorgan dysfunction syndrome (MODS) through lactic acidosis, inflammation, and peroxidation (Matsuo et al, 2021; Wagner et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…FSN acts mainly in the subcutaneous layer (Yu et al, 2019) and does not penetrate the muscular layer. Research has indicated that FSN can relieve pain and improve soft tissue pathology related to injury in clinical practice (Liu et al, 2019). To our knowledge, there is no published evidence-based literature on FSN effects related to shoulder pain.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, acupuncture has become an increasingly popular technique and is used worldwide for the management of pain, headache, musculoskeletal diseases, and other health problems (27). Previous studies demonstrated that acupuncture is effective and safe for PSSP, especially in reducing pain intensity (27)(28)(29)(30). It has been incorporated into some guidelines as adjuvant therapy for PSSP (31).…”
Section: Introductionmentioning
confidence: 99%